IMPLEMENTATION OF AUTOMATIC PLANT SPRINKLERS USING SOIL MOISTURE SENSORS - Yessi Jusman; Slamet Suripto; Naufal Hadiansyah; Masayu Alya Nur'aini; Wikan Tyassari (LPPM Universitas Abdurrab, 2024)
Automatic plant sprinklers aim to replace manual work into automatic, as for the benefits obtained from this tool is that it can facilitate human work in watering onion plants. This tool uses a soil moisture sensor that functions as a soil moisture detector and sends commands to Arduino uno to turn on the relay so that the pump can turn on and splash water according to soil needs automatically. The design of this tool utilizes the nature of water, which is to fill empty space, and is always flat, this automatic plant sprinkler uses a water reservoir before water is splashed on the ground. Output holes applied to water reservoirs of the same height and diameter allow watering of the soil evenly. The results of the automatic plant sprinkler design test obtained after three tests, have a difference in the amount of water released from water hole one and water hole two, which ranges from 0-7%, which means it is still within the tolerance limit for onion plants, onion plants need soil moisture between 70-80%, which means it has a moisture tolerance between 10%.